Analisis Gambaran Terapi dan Interaksi Obat pada Pasien Mixed Anxiety and Depressive Disorder di Rumah Sakit Islam Arafah Kota Jambi Tahun 2021-2023 - Andriani, Medi; Sanuddin, Mukhlis; Umairoh, Sarah (Jurnal Farmasi (Journal of Pharmacy), 2025)
Mixed Anxiety and Depressive Disorder (MADD) is a condition in which individuals experience symptoms of anxiety and depression simultaneously, but do not meet all the diagnostic criteria for anxiety disorders and depressive disorders. When symptoms of anxiety and depression appear together, it will cause a significant decline in function for the sufferer. In 2015, it was estimated that more than 300 million people worldwide suffered from depression and anxiety. Based on data from Kementerian Kesehatan Repbulik Indonesia, the prevalence of depression in Jambi Province is 1.8%. During the COVID-19 pandemic, the prevalence of anxiety was found to be 32.2%. This study aims to analyze the therapeutic features and potential drug interactions in MADD patients at the Rumah Sakit Islam Arafah, Jambi City. The research sample consisted of 153 patients diagnosed with MADD in 2021-2023. Data collection in the study used a retrospective method, namely searching secondary data from medical records. Research results show that concoction prescriptions are widely prescribed in 2021-2023, namely 52%, 52% and 50% respectively. The classes of drugs prescribed for MADD sufferers in 2021-2023 are antidepressants and benzodiazepines. The most frequently prescribed drug classes for patients with comorbidities are antipsychotics at 16%, 17% and 18% respectively and antihypertensives at 3% in 2021-2023. The drugs most commonly prescribed in 2021-2023 are sertraline at 14%, 14%, 11% and alprazolam at 13%, 13% and 15%. The prescribed dose of sertraline is 50 mg and alprazolam 0.25 mg, 0.5 mg and 1 mg. The frequency of sertraline prescribed is 1x per day and 2x per day. The frequency of alprazolam prescribed is 1x per day and 2x per day. The most cases of drug interactions are at the moderate level (aripiprazole-sertraline) at 7% and 8% in 2021 and 2022, while in 2023 it will be 9% (alprazolam-aripiprazole).